JAEPL, Vol. 19, Winter 2013-2014 - Joona Smitherman Trapp; Brad Peters (Journal of the Assembly for Expanded Perspectives on Learning, 2013)
Essays Peter Elbow - Using Careless Speech for Careful, Well-Crafted Writing - Whatever Its Style Keith Rhodes & Monica M. Robinson - Sheep in Wolves' Clothing: How Composition's Social Construction Reinstates Expressivist Solipsism (And Even Current-Traditional Conservatism) Bradley Smith - The Journey Metaphor's Entailments for Framing Learning Sarah Hochstetler - A Teacher's Terminal Illness in the Secondary Classroom: The Effects of Disclosure Anna O. Soter - It's (Not) Just a Figure of Speech: Rescuing a Metaphor Amy L. Eva, Carrie A. Bemis, Marie F. Quist, & Bill Hollands - The Power of the Poetic Lens: Why Teachers Need to Read Poems Together Ryan Crawford & Andreas Willhoff - Stillness in the Composition Classroom: Insight, Incubation, Improvisation, Flow, and Meditation Kathleen J. Cassity - Fear Not the Trunchbull: How Teaching from a Humorous Outlook Supports Transformative Learning Sharon Marshall - Thoughts on Teaching as a Practice of Love Out of the Box Ilene Dawn Alexander - Learning and Teaching in Other Ways Book Reviews Judy Halden-Sullivan - Making the Familiar Unfamiliar Karen Walker - Ritchhart, Ron, Mark Church, and Karin Morrison. Making Thinking Visible. San Francisco, CA: Jossey-Bass, 2011. Timothy Shea - Jobrack, Beverlee. Tyranny of the Textbook. New York: Rowman & Littlefield Publishers, Inc., 2012. Julie Nichols - FitzGerald, William. Spiritual Modalities: Prayer as Rhetoric and Performance. University Park, PA: Penn State Press, 2012. Edward Sullivan - Quesada, Donna. The Buddha in the Classroom: Zen Wisdom to Inspire Teachers. NY: Skyhorse Publishing, 2011. Connecting Helen Walker - Gratitude Bob Randolph - Poetry Teacher's Prayer Leigh Ann Chow - What Teachers Carry Andrea Saylor - A Brief History of Holy Writing Jill Moyer Sunday - For My Students Kattie Hogan & Matt Ittig - Lines on the Body: Confronting Personal Experiences through Poetry John Patrick Cleary - New Teacher